Biomass and Carbon Stock Assessment in Different Age Group Plantations of Teak (Tectona grandis Linn. F.) in Bhabar and Shivalik Regions of Uttarakhand - Nirala, Deepshikha; Khanduri, V. P.; Sankanur, M. S. (International Journal of Bio-resource and Stress Management, 2018)
The available information on optimum rotation of teak is largely based on teak plantations. Age at which a tree stand is extracted decides the quality of the timber; biomass accumulation and carbon sink potential of the stand. The present study was based on non-destructive method to assess the total biomass, carbon stock and carbon dioxide (CO2)content of different age group plantations of teak at five different compartments of Bhabar and Shivalik regions of Kotdwar Forest Division, Uttarakhand. Above ground biomass (AGB), below ground biomass (BGB) and total biomass (TB) significantly influenced by different sites and age group of teak plantations. The extent of increase in AGB (687.07 t ha-1), BGB (171.77 t ha-1) and TB (858.84 t ha-1) in S26 (Sigaddi-18A) plantation site at the age of 48 was 70.10% over S8 (Sigaddi-18B) in AGB (205.40 t ha-1), BGB (51.35 t ha-1) and TB (256.75 t ha-1) at the age of 33 years. Further, the total carbon (TC) (429.42 t ha-1) and CO2 (1575.97 t ha-1) was highest in Sigaddi-18A (S26)plantation site at the age of 48 years. Whereas, the lowest TC (128.37 t ha-1) and CO2 (471.13 t ha-1) at the age of 33 years was observed in S8 (Sigaddi-18). The tree diameter (cm) showed highly significant positive correlation with volume (R2=0.903), total biomass as well as with total carbon (R2=0.859). The variation in diameter could explain nearly 85.9 % variation in total biomass and total carbon. Therefore, the diameter can be a good predictor of biomass and carbon sequestration in teak plantations.